What have we learned from long-term studies in juvenile idiopathic arthritis? – Prediction, classification, transition. - Marite Rygg; Filipa Oliveira Ramos; Ellen Berit Nordal (Pediatric Rheumatology Online Journal)
Abstract Background Research and management of juvenile idiopathic arthritis (JIA) are challenging due to its heterogeneous nature, chronicity, and unpredictable, multidimensional long-term outcomes. Main body Long-term studies have consistently shown that a majority of children with JIA reach adulthood with ongoing disease activity, on medication, or with recurrent flares. The heterogeneity is evident both between and within the present JIA categories based on The International League of Associations for Rheumatology (ILAR) JIA classification system. Several baseline predicting factors are known, but prediction modelling is only in the initial phase, and more models need to be tested in independent cohorts and possibly also supplemented with new biomarkers. Many have criticized the ILAR classification system, but new or updated classification systems have not yet been validated and proved their superiority. The lack of prediction possibilities for long-term outcomes and the limited alignment between JIA classification categories and adult rheumatic conditions are challenges for research, may limit the accessibility to treatment, and hamper a smooth transition to adult care. Conclusion We need more prospective, long-term studies based on unselected JIA cohorts with disease onset in the biologic era that can aid decision-making for individualized early treatment, suggest intervention studies, and ensure our patients the best possible transition to adulthood and the best likelihood of optimal health and quality of life.